下唇に生じた唾石を伴う粘液囊胞の1例 - 石田, 尚子; 八木原, 一博; 道, 泰之; 炭野, 淳; 依田, 哲也; 柴田, 真里 (日本口腔外科学会雑誌, 2019)
Sialoliths mainly occur in the major salivary glands and rarely arise in the minor salivary glands. Sialoliths in the lower lip are extremely rare, and only one case of histopathological mucous cyst with sialolith of the lower lip has been reported in Japan including reports from overseas.　We report a case of mucous cyst associated with a sialolith of the lower lip. A 71-year-old woman referred to our university hospital for a tumor mass of the left side of the lower lip. The clinical diagnosis was a benign tumor. We extirpated the tumor. There were no adhesions of the surrounding tissue, and the tumor was extirpated without any problem. Histologically, a cystoid structure was observed. Mucus containing neutrophils and foam cells was stored in the cyst, and it contained calcified material. The histological diagnosis was a mucous cyst with a sialolith of the lower lip. The patient’s postoperative course has been good, with no evidence of recurrence as of 1 years 3 months after surgery.